An unusual richness, structure and composition tree in terra firme forest of Pongo Qoñec, Peruvian South East - Huamantupa-Chuquimaco, Isau (2010)
One plot of 1 ha, was established in the terra firm forest in the Pongo de Qoñec, Kosñipata valley (Cusco), inside the reserve Biósfera of the Manú, to 710 m; 12°53'53"S and 72°22'25"W. We registered, 56 families, 153 genus, 249 species, with 813 individuals with Dap ≥ 10 cm. Families, more rich were: Fabaceae (32 species), Moraceae (24), Rubiaceae (17) and Lauraceae (12); The most rich genus were, Inga (17), Neea (7), Miconia (5); the total basal area was 40.50 m2, of them Iriartea deltoidea with 6.58 m2, Socratea salazarii 2.28 m2, and Endlicheria sp 1.65 m2, obtained bigger ab; The specie with most high value of importance went: I deltoidea, corroborating previous studies in the terra firm forests. The structural analysis evidences than diametrics class of 10-20 cm, was 71.3 % of the total of individuals. When comparing our results, the Pongo Qoñec, surprisingly obtained high richness to adjacent plots, inside the Peruvian south and sample a similar patterns of richness of families and genus to most diversity Peruvian plots how Yanamono 300 species and Mishana (289), in Loreto. We considered that these unusual richness are due to environmental factors, present in the Pongo de Qoñec, such as the high precipitation, dynamics of winds and the variability of soils in little areas. Therefore these results differ considerably from known enunciates, that consider that Amazon south Peruvian have low and moderate trees richness.